DINACHARYA MODALITIES - A REVIEW ON EVIDENCE BASED RESEARCH W. S. R TO ORAL HYGIENE (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda recognizes oral cavity as one of the nine openings of physical body and also stressed that these openings are full of blemishes with their secretions throughout day and night, hence it suggests cleaning these openings frequently and regularly. Oral cavity being the chief entrance of the main gateway, as it were to the body, should be kept healthy from the attack of enemies of health. Ayurveda prescribes Dinacharya modalities like brushing the tooth (Dantadhavana), gargling (Kavala and Gandoosha) to keep up the health of the oral cavity, prevention and treatment of diseases of the oral cavity. Researchers have shown that all kinds of chewing sticks (Dantadhavanakashta) and gargling especially with sesame oil (oil pulling) described in Ayurveda texts have anti- plaque and antimicrobial activity thus promote oral hygiene. Use of safe, quality products and practice must be ensured, based on available evidence and traditional medicine has to be acknowledged as part of primary health care. It is also required to ensure patient safety by upgrading the skills and knowledge of the traditional medicine providers. Scientific validation of the Ayurveda oral health practices given above could justify their incorporation in to modern oral health care. Publicity of these techniques using appropriate media would benefit the general population by giving more confidence in ancient practices, thus preventing the decay and loss. The preparation of standard protocol for implementation of these modalities in the community is need of the hour.